Associations of NT-proBNP and parameters of mental health in depressed coronary artery disease patients. (October 2018) - Fangauf, Stella V.; Herbeck Belnap, Birgit; Meyer, Thomas; Albus, Christian; Binder, Lutz; Deter, Hans-Christian; Ladwig, Karl-Heinz; Michal, Matthias; Ronel, Joram; Rothenberger, Aribert; Söllner, Wolfgang; Wachter, Rolf; et al.
Highlights: In depressed CAD patients, serum NT-proBNP is associated with better mental health. Patients with higher levels of serum NT-proBNP experience less bodily pain. BNP peptide may have a protective function against psychosocial distress. Abstract: Natriuretic peptides (NP) are involved in the regulation of blood pressure and blood volume, and are elevated in patients with coronary artery disease (CAD). They are used as markers for illness severity, but their role in mental health is not well understood. Recently, A-type NP (ANP) has been associated with reduced anxiety in studies on cardiac patients; however, this study is the first to assess this effect for B-type NP (BNP) and for further dimensions of well-being and mental health. Depression, anxiety, and distress are more common in CAD patients than in the general population and are most likely not only influenced by psychological adaptation but also by neurobiological processes. We used baseline N-terminal proBNP (NT-proBNP) samples and psychometric assessments of 529 at least mildly depressed (Hospital Anxiety and Depression Scale, depression score ≥ 8) CAD patients from the multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial. Psychosocial status was assessed using standardized self-rating questionnaires on anxiety, depression, coping with illness, vital exhaustion, type D personality, and quality of life. Separate linear regression models for each psychometric scale revealed significant negative correlations of NT-proBNP with anxiety, depression, vital exhaustion, depressive coping, and negative affectivity. Moreover, patients with higher levels of NT-proBNP experienced less bodily pain and had a better self-rated mental health, despite worse physical functioning. Linear regression adjusted for age, sex, and physical functioning (Short Form Health Survey [SF-36]) revealed NT-proBNP to be a significant predictor for all tested measures of the patients' psychosocial status. These results indicate that NT-proBNP is not only positively associated with greater disease severity in mildly to moderately depressed CAD patients but also with better psychosocial status and mental well-being. Possible mechanisms of this effect are discussed.